A matrisomal proteomics network modulates tau and amyloid‐beta toxicity in fly AD models. (20th December 2022) - Li‐Kroeger, David; Al‐Ramahi, Ismael; Marella, Aditi; Amoh, Bismark K; Smith, Nathaniel; Botas, Juan; Seyfried, Nicholas T.; Levey, Allan I.; Shulman, Joshua M
Abstract: Background: Mounting evidence indicates Alzheimer's disease (AD) has a complex etiology where insults in multiple pathways conspire to disrupt neuronal function, yet the molecular changes underlying AD remain poorly understood. To identify protein changes associated with AD, we previously performed mass‐spectrometry on post‐mortem brain tissue from longitudinal cohorts and identified >40 protein coexpression networks correlated to AD pathological and clinical traits. A small module (M42) consisting of 37 proteins linked to the extracellular matrix (ECM/matrisome) has the strongest correlation to AD pathology (r=0.75), and includes several proteins linked to AD (e.g. APP, APOE) including SMOC1 as the central hub. SMOC1 has conserved roles in modulating TGF‐Beta and wnt signaling during development, however, its role in the adult brain remains unstudied. Method: We evaluate the SMOC1 associated protein network using the powerful genetics of Drosophila to characterize its role in neuronal function and uncover links to specific triggers of AD. We use a high‐throughput robotic screening platform and video assisted software which enables robust, quantitative assessments of neurological function to identify conserved members of M42 that modify Amyloid‐Beta‐ or tau‐induced neurodegeneration. Using a combination of loss‐of‐function alleles and RNA interference (RNAi) we tested over 200 transgenic fly lines, representing 47 Drosophila genes corresponding to 37 human proteins nominated from the M42 ECM network. Result: We found that SMOC1 knock‐down modifies tau toxicity using RNAi and loss‐of‐function alleles, confirming a link to specific AD triggers. In addition, we identified 13 other genes with robust evidence of interactions with either tau or Aβ in our fly models including multiple wnt signaling components and TGF‐β ligands. Additionally, we begin characterizating the fly ortholog dSMOC1 showing expression in a small subset of neurons and many glial cells in the brain. Finally, we show human SMOC1 can rescue lethality caused by complete loss of dSMOC1 function, thus setting the stage for mechanistic analysis. Conclusion: The M42 protein coexpression network contains multiple proteins with links to AD and our screening pipeline identified multiple conserved ECM proteins interacting with specific AD triggers. This analysis helps diversify the pool of potential therapeutic targets for the fight to cure AD.